Food intake and oral health status of inpatients with dysphagia in acute care settings. (18th April 2020) - Furuya, Junichi; Suzuki, Hiroyuki; Tamada, Yasushi; Onodera, Shohei; Nomura, Taro; Hidaka, Rena; Minakuchi, Shunsuke; Kondo, Hisatomo
Abstract: Adequate oral status and functional assessments are important for dysphagia rehabilitation in acute care inpatient settings, especially to establish individualised oral intake. However, the association between food intake levels and oral function has not been elucidated in acute care inpatients. This cross‐sectional study clarified the association between oral intake levels and the oral status/function of patients with dysphagia admitted to acute care settings. Admitted patients aged ≥40 years (n = 459; men: 288; mean age: 70.8 ± 12.0) examined at the Department of Dysphagia Rehabilitation at the Iwate Medical University Hospital from April 2007 to March 2014 were included. The oral health status was evaluated by the tongue coating, oral dryness severity, plaque control, posterior occlusal support and a repetitive saliva swallowing test (RSST). Dysphagia severity was determined from the Dysphagia Severity Scale. Oral intake levels were evaluated using the Functional Oral Intake Scale (FOIS) at the time of the initial dental examination (FOIS‐I), and they were re‐evaluated after the revision of levels according to the participants' general condition and oral health status (FOIS‐R). Divergence between FOIS‐I and FOIS‐R was noted in >40% patients. Multiple regression analysis showed significant associations between FOIS‐R and consciousness level, activities of daily living, tongue coating, RSST and posterior occlusal support. Patients with dysphagia in acute care settings require detailed assessments of their oral status and function, including swallowing, to determine the most suitable feeding methods and dental interventions to improve oral intake levels.